Advancing the JUNGFRAU detector toward low-energy X-ray applications. (27th September 2022) - Hinger, V.; al Haddad, A.; Barten, R.; Bergamaschi, A.; Brückner, M.; Carulla, M.; Chiriotti-Alvarez, S.; Dinapoli, R.; Ebner, S.; Fröjdh, E.; Greiffenberg, D.; Hasanaj, S.; et al.
Abstract: The charge-integrating hybrid silicon pixel detector JUNGFRAU has found widespread use at free-electron laser and synchrotron facilities. The detector was designed for use with hard X-rays; yet, because of its low noise, high dynamic range, position resolution, and scalable size, JUNGFRAU is of high interest for soft X-ray applications. We discuss improvements of the readout chip and alterations of the entrance window at the back of the sensor that facilitate low-energy X-ray detection. The first use case of the improved system at a low-energy beamline demonstrates single photon sensitivity down to 800 eV. At lower energies, the readout noise of the hybrid detector hinders the resolution of single photons. We propose to couple the JUNGFRAU readout chip with charge-multiplying low-gain avalanche diode (LGAD) sensors to resolve X-ray photons with a minimum energy of 250 eV.